TELAAH ABSURDITAS ALBERT CAMUS DALAM NOVEL CARA BERBAHAGIA TANPA KEPALA KARYA TRISKAIDEKAMAN: TINJAUAN PSIKOANALISIS - St. Adawiyah Arisa; Muhammad Rapi Tang; Hajrah Hajrah (Universitas Negeri Makassar)
Study of Albert Camus' Absurdity in the Novel Cara Berbahagia Tanpa Kepala: Psychoanalytic Riview. This research aims to study the validity in the novel Cara Berbahagia Tanpa Kepala by Triskaidekaman based on the context of absurdity thought announced by Albert Camus with the concept of Freud. The method used is qualitative which is descriptive. Data is collected using reading and note-recording techniques. Analysis of character characters in the novel Cara Berbahagia Tanpa Kepala by Triskaidekaman which is associated with the theory of absurdity camus is about rebellion and the results of this study showed that the rebellion contained in the character characters in the novel Cara Berbahagia Tanpa Kepala by Triskaidekaman, this led them to the creation of a new meaning of happiness, in accordance with the theory of absurdity Camus later developed with the concept of Freud.